2008
DOI: 10.2134/jeq2006.0562
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Fate and Transport of Metolachlor in the Unsaturated Zone, Maryland, USA

Abstract: An unsaturated-zone transport model was used to examine the transport and fate of metolachlor applied to an agricultural site in Maryland, USA. The study site was instrumented to collect data on soil-water content, soil-water potential, ground water levels, major ions, pesticides, and nutrients from the unsaturated zone during 2002-2004. The data set was enhanced with site-specific information describing weather, soils, and agricultural practices. The Root Zone Water Quality Model was used to simulate physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 44 publications
1
24
0
2
Order By: Relevance
“…Initial versions of the models at C22 and M21 were predicated on manually calibrated models from previous studies (Bayless et al, 2008; Domagalski et al, 2008) and were altered as necessary to confine estimates of N mass balances to the unsaturated zone. We specified a unit gradient boundary condition for the lower boundary at all four sites to allow free drainage and keep the water table below the simulated profile.…”
Section: Methodsmentioning
confidence: 99%
“…Initial versions of the models at C22 and M21 were predicated on manually calibrated models from previous studies (Bayless et al, 2008; Domagalski et al, 2008) and were altered as necessary to confine estimates of N mass balances to the unsaturated zone. We specified a unit gradient boundary condition for the lower boundary at all four sites to allow free drainage and keep the water table below the simulated profile.…”
Section: Methodsmentioning
confidence: 99%
“…Like nitrate-N, MESA is very soluble (2.12*10 5 mg/L) (Bayless et al, 2008), has a low sorption coefficient (calculated log K oc = 1.13) (Bayless et al, 2008), and has been classified as highly mobile Domagalski et al, 2008;Huntscha et al, 2008). In contrast to nitrate-N, once MESA enters ground water, it is very stable (Phillips Table 1 Conceptual model of landscape characteristics that influence transport, processing, and delivery of nitrate-N and MESA to headwater streams of the Choptank River (Ator et al, 2005;Bachman and Phillips, 1996;Denver et al, 2010, in press;Phillips and Bachman, 1996;Phillips et al, 1993 Steele et al, 2008); MESA persists over decadal time scales (Denver et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…MESA formation has been shown to occur in the upper aerobic-layer of the soil column (Baran and Gourcy, 2013;Bayless et al, 2008;Denver et al, 2004;Denver et al, 2010;Domagalski et al, 2008;Huntscha et al, 2008). In a multi-year field and modeling study, Bayless et al (2008) found that metolachlor was very transient with a simulated half-life of 10 days and that MESA was rapidly formed in the first meter of the soil and was leached to the water table within 1-2 years. This rapid transformation of metolachlor to MESA led to high concentrations of MESA in the water table beneath the field.…”
Section: Sf Values For Metolachlor and Mesa In Stream Samplesmentioning
confidence: 99%
“…After application, metolachlor is readily transported into the soil where it is transformed into several compounds, the most abundant being, metolachlor ethane sulfonic acid (2-[(2-ethyl-6-methylphenyl)(2-methoxy-1-methylethyl)amino]-2-oxoethanesulfonic acid, MESA) (Baran and Gourcy, 2013;Bayless et al, 2008;White et al, 2010). MESA can be found in groundwater wherever metolachlor has been used and it appears to be quite stable in groundwater (Baran et al, 2004;Barbash et al, 1999;Bayless et al, 2008;Denver et al, 2010;Domagalski et al, 2008;Huntscha et al, 2008;Kalkhoff et al, 2012;Krutz et al, 2006;Rebich et al, 2004;Hancock et al, 2008).…”
Section: Introductionmentioning
confidence: 99%